Land rights for widows? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
If a woman loses her husband, she is also at risk, in many countries, of losing the land and property on which her survival depends. Prisca Ngum, a widow in Cameroon, describes her experience, and questions the tradition that widows should have no rights to their late husband?s property.